Banking concentration and financial stability: Evidence from developed and developing countries - Mohamed Sami Ben Ali; Timoumi Intissar; Rami Zeitun (Kiel Institute for the World Economy (IfW), 2015)
In this paper, the authors analyze the relationship between banking concentration and financial stability for a sample of 173 developed and developing countries over the period 1980-2011. First, they empirically examined the direct effect of banking concentration on financial stability by using a panel logit model. Second, the authors investigated the indirect effect through which concentration may affect stability. Their findings provide support for the existence of both concentration-stability and concentration-fragility channels. However, the authors report the absence of any direct effect of banking concentration on the occurrence of financial stability in our sample. When considering heterogeneity across countries, their results help confirm the stabilizing effect of concentration on financial stability for developing countries. However, the concentration-fragility hypothesis does not hold for these countries. They also confirm the existence of both effects regarding concentration: the stabilizing and destabilizing effect of concentration on financial stability.
Keywords: E31; E3; C33; P44; 330; Banking structure; Financial stability; Panel logit; GMM model